Long Non-Coding RNA: A Potential Strategy for the Diagnosis and Treatment of Colorectal Cancer - Chen, Shanshan; Fang, Yi; Sun, Lingyu; He, Ruonan; He, Beihui; Zhang, Shuo (Frontiers in Oncology, 2021)
Colorectal cancer (CRC), being one of the most commonly diagnosed cancers worldwide, endangers human health. Because the pathological mechanism of CRC is not fully understood, there are many challenges in the prevention, diagnosis, and treatment of this disease. Long non-coding RNAs (lncRNAs) have recently drawn great attention for their potential roles in the different stages of CRC formation, invasion, and progression, including regulation of molecular signaling pathways, apoptosis, autophagy, angiogenesis, tumor metabolism, immunological responses, cell cycle, and epithelial-mesenchymal transition (EMT). This review aims to discuss the potential mechanisms of several oncogenic lncRNAs, as well as several suppressor lncRNAs, in CRC occurrence and development to aid in the discovery of new methods for CRC diagnosis, treatment, and prognosis assessment.